Dedifferentiated Liposarcoma of the Spermatic Cord: A Series of 42 Cases. (September 2015) - Kryvenko, Oleksandr N.; Rosenberg, Andrew E.; Jorda, Merce; Epstein, Jonathan I.
Abstract : Dedifferentiated liposarcoma (DDL) of the spermatic cord is rare, with limited data regarding morphology and prognosis. We analyzed the morphologic spectrum of DDL of the spermatic cord and its clinical significance in 42 patients from 1990 to 2014. The median age of the patients was 70.5 years (range: 43 to 90 y). The median tumor size was 10.9 cm (range: 3 to 30 cm). Six cases were low-grade DDL, 28 were high-grade DDL, and in 8 cases both coexisted. Five cases had osteosarcoma, and 2 had leiomyosarcoma differentiation. Low-grade DDL had a fibrosarcoma-like (n=11), myxofibrosarcoma-like (n=2), and fibrosarcoma and inflammatory-like (n=1) pattern. High-grade DDL had a fibrosarcoma-like (n=22), undifferentiated pleomorphic sarcoma-like (n=7), myxofibrosarcoma and undifferentiated pleomorphic sarcoma-like (n=4), fibrosarcoma and undifferentiated pleomorphic sarcoma-like (n=2), and myxofibrosarcoma-like (n=1) pattern. Resection margins were positive in 22, negative in 13, and unknown in 7 cases. MDM2 was positive in 24/24 cases. Two patients received neoadjuvant radiotherapy (1 with chemotherapy). Patients received postoperative radiation (n=13), reexcision (n=5) with radiation (n=3), chemotherapy (n=2), chemotherapy and radiation (n=1), no therapy (n=11), and unknown (n=6). Follow-up information was available in 31 patients (mean: 54.2 mo; median: 38.5 mo; range: 2 to 180 mo). Seven patients developed local recurrence. Two patients had systemic metastases and succumbed to disease. Recurrence developed at an average of 40.9 months (median: 24 mo; range: 12 to 100 mo) after resection. Average follow-up in patients without recurrence was 45.2 months (median: 25 mo; range: 2 to 180 mo) ( P =0.87). Margin status, size, and grade did not correlate with recurrence ( P >0.05). Thus, DDL of the spermatic cord includes a spectrum of morphologic patterns. Complete excision is difficult at first attempt. Local recurrence is common, and relatively few patients develop systemic disease.